PEMBUATAN GAME STRATEGI THRONES AND CASTLES DENGAN FITUR VOICE COMMAND - Nikolas Arif; Budi Hartanto; Marcellinus Ferdinand Suciadi (CALYPTRA, 2018)
Abstract - A game needs an input from the p ayer to respond. Most used input types are mouse and keyboard. G mes also have other inputs such as touch screen, and voice input. According to data from Steam, several games using voice input feature have a lot of positive review from players. However the number of games using voice input feature remain quite low. The creation of strategy game Thrones and Castle is intended to give a special attractiveness in strategy game using voice input feature. This game is created using Unity Game Engine, with the addition of voice input feature in game. Analysis and design process was done by comparing two existing games with similar feature. Design result was implemented using Unity Game Engine. Implementation result was tested to ensure the game have reached its goal. Testing was done by asking eighteen respondents to try the game and answer a questionnaire. Questionnaire result as a whole shows that voice input feature can give attractiveness to the game, moderately easy to use and quite accurate. Furthermore, writer also tested every available feature in game. After tests were completed, writer concludes that the game has reached its goal.